Mouse Models in Autoimmune Disease Studies: Reproducibility and Clinical Applications - Muhammad Faldy Abdul Aziz; Malika Adira Hasri; Nany Hairunisa; Nor Azlina Khalil; Rodiah Mohd Radzi; Dyah Ayu Woro Setyaningrum (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Objective: Autoimmune diseases are complex disorders that arise when the immune system loses tolerance to self-antigens, leading to chronic inflammation and tissue damage. To understand disease pathogenesis and to evaluate therapeutic efficacy, animal models are widely used in autoimmune research. This review aims to analyze various types of animal models employed in studies of autoimmune diseases such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), type 1 diabetes mellitus (T1DM), and multiple sclerosis (MS), with a particular focus on reproducibility and clinical applicability. Methods: This study was conducted through the selection and analysis of scientific literature published over the last ten years (2015–2025), using specific keywords including “clinical application,” “autoimmunity,” “animal models,” “humanized mice,” “lupus,” “rheumatoid arthritis,” “reproducibility,” and “translational research.” Literature searches were performed in major databases such as Google Scholar, PubMed, ScienceDirect, and Scopus. Results: Spontaneous models, such as NOD and MRL/lpr mice, exhibit close resemblance to human disease pathogenesis but are influenced by strain variability and environmental factors. Induced models, including collagen-induced arthritis (CIA) and experimental autoimmune encephalomyelitis (EAE), allow greater control over disease onset but do not fully capture the clinical complexity observed in humans. Humanized models demonstrate high translational relevance; however, their use is constrained by high costs and technical limitations. Conclusion: No single animal model is universally ideal for studying autoimmune diseases. Model selection should be based on biological relevance, reproducibility of outcomes, and the potential for clinical translation in autoimmune disease research.